Effects of the film thickness on optical constants of transparent CdS thin films deposited by chemical bath deposition - Yakuphanoğlu, Fahrettin; Viswanathan, C.; Peranantham, P.; Soundarrajan, D. (Natl Inst Optoelectronics, 2009)
The optical constants and band gaps of the CdS thin films deposited by chemical bath have been calculated in the spectral wavelength range 400-1000 nm from the transmittance and reflectance measurements of normally-incident light. The CdS thin films exhibit good transparent behavior due to high transmittance values. The optical band gaps of the films were respectively found to be 2.34, 2.41 and 2.46 eV for 100, 125 and 152 nm thicknesses. The increase in film thickness leads to an increase in optical band gap of the films. The refractive index values of the thin films changed significantly with film thickness. The dielectric constant of the films was analyzed using Standard Drude model. The optical carrier concentration and mobility values for the CdS thin films were determined and the obtained values changed with film thickness. It is shown that the film thickness modifies the optical constants and band gaps of the CdS films.
Keywords: Optical constants; optical band gap; CdS thin films